Kosmos i filozofia – kilka uwag na temat „niepokoju kosmologicznego” Stanisława Ignacego Witkiewicza - Szynkiewicz, Mariusz (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
Stanisław Ignacy Witkiewicz was one of the greatest and unconventional artists of his generation. This text pertains to philosophical aspects of S.I. Witkiewicz literature. The author’s philosophical vision of cosmos and sense of human live is examined from the perspective of a claim that philosophical contemplation is inherent in the cosmological contexts of Witkiewicz’s novels.